Post-Colonial Trinidad - Clarke, C. author. aut Link
XXII, 246 p.
Keywords: Clarke and Clarke have created a journal that provides an ethnographic record of the East Indians and Creoles of San Fernando - and the entire sugar belt south of the town known as Naparima. They record socio-political relations during the second year of Trinidad s independence (1964), and provide first-hand evidence for the workings of a complex, plural society in which race, religion, and politics had become, and have remained, deeply intertwined. Entries occur whenever there is evidence of social scientific importance to the project, and these range from descriptions of weddings and pujas (prayer ceremonies devoted to a Hindu deity) to interviews with religious leaders, politicians and members of the south Trinidad elite.